Walking on air : the aerial adventures of Phoebe Omlie - Sherman, Janann (Willie Morris books in memoir and biography., 2011)
Aviation pioneer Phoebe Fairgrave Omlie (1902-1975) was once one of the most famous women in America, regarded as second only to Amelia Earhart among America's women pilots. She earned the first commercial pilot's license issued to a woman and became a successful air racer. During the New Deal, she became the first woman to hold an executive position in federal aeronautics. This book presents a thorough biography of Omlie.